Design of reverse flow ambient air heated vaporizer under different ambient temperatures and optimization of the fin arrangement. (1st September 2022) - Jadav, Chirag; Chowdhury, Kanchan
Highlights: Reverse flow system is preferable for the ambient temperature above 281 K. Heat transfer is augmented by providing lower number of fins in the frosted region. Higher number of fins to be used to augment heat transfer in no-frost segment. Optimized number of fins and fin height vary depending on the location of the tube. Optimized multi-fin system can augment the heat transfer throughout the vaporizer. Abstract: Ambient air heated cryogenic vaporizers utilize aerothermal energy from the environment and re-gasify stored liquefied industrial gases. In a conventional system, there are two vaporizer blocks: one remains active, while the other gets defrosted. There is often an idle time in the defrosting process that the reverse flow vaporizer proposes to eliminate. As the thickness of frost over the surface of finned tubes varies from inlet to outlet points, optimized number of fins and their height also vary throughout the vaporizer block. In the literature, optimization process keeps the fin specification identical for all the tubes. However, a varying frost thickness along the vaporizer length provides an opportunity to augment the heat transfer by optimizing each finned tube based on the frost deposition over it. One dimensional heat transfer model of defrosting is developed and solved implicitly using the central difference method. Genetic Algorithm optimizes each tube of the vaporizer based on its location inside the block and minimizes its weight which is 16% lower than that of the single-fin reverse flow system and 35% lower than that of the single-fin conventional ambient air heated vaporizer. This would lead to large savings in the capital cost of the vaporizers.